Identification of Tourism Components of Tourism Villages in Supporting Tourism Development in the New Normal Era: Kerta Village Gianyar Bali - Ni Putu Tiya Paristha; Ni Kadek Sri Mirayani (PROGRAM STUDI PARIWISATA SYARAH, FAKULTAS EKONOMI DAN BISNIS ISLAM, UNIVERSITAS ISLAM NEGERI MATARAM, 2022)
Purpose: This study aims to identify the destination components in Kerta Tourism Village, Gianyar, Bali to support the development of tourist villages in the new normal era. The focus of this study is to determine the attractiveness analysis based on four aspects of tourist destination components by using Tourism Destination Development Theory, which focuses on attraction, amenities, accessibilities, and ancillary. Methods: The data were collected by the observation, in-depth interviews, and document studies. Furthermore, the data that has been collected will be analyzed using qualitative descriptive analysis techniques. Results: The success of developing a tourism village can be seen in the benefits of managing its potencies to improve the welfare of local community. Kerta Tourism Village has developed four aspects of tourist destination components. There are three types of tourist attractions that can be found, namely natural attractions, cultural attractions, and man-made attractions. The supporting facilities are still limited, and generally provided and owned by the private, therefore it does not provide economic benefits for the community. Kerta village has good accessibility, making it easier for tourists to use various types of transportation. However, the limited street lighting should be a concern for the villager. For the ancillary aspect, the tourism village is managed by Pokdarwis, a community that formed to mobilize community participation to jointly develop tourism potential in the village. Tourism villages can be an alternative tourism destination in this new normal era since they are closely related to nature and cultural elements as well as several sites in a tourism village. Therefore, it is feasible to develop a tourism village by following standard health protocols in the era of adaptation to new and post-pandemic habits to assures tourists travel safely in tourist villages. Contribution: Practically, this study is expected to be a recommendation for stakeholders in efforts to develop tourist destinations, especially for those involved in developing the Kerta Tourism Village.